2022
DOI: 10.1039/d2nj02725a
|View full text |Cite
|
Sign up to set email alerts
|

The selective production of CH4via photocatalytic CO2 reduction over Pd-modified BiOCl

Abstract: Photocatalytic CO2 reduction to CH4 is a promising strategy to convert the main green gas of CO2 for the net-zero emission future. However, efficient photocatalysts with high selectivity are still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Under AM 1.5G illumination, the Eu 2 Ti 4 dispersed on FTO showed a 0.009 μmol h –1 cm –2 CH 4 production rate and a 0.037 μmol h –1 cm –2 CO production rate for photocatalytic CO 2 reduction in a water vapor atmosphere (Figure f), with a solar-to-fuel (STF) efficiency of 0.0046% (Figure S3). The photocatalytic performance of Eu 2 Ti 4 on an Au-coated FTO substrate is illustrated in Figure S4a, showing an increased selectivity for CH 4 following the Au coating, suggesting that Au can facilitate the separation of electron–hole pairs for CH 4 formation which needs more active electrons. , Moreover, when dispersed in pure water under a CO 2 atmosphere, Eu 2 Ti 4 demonstrated production rates of 2.02 μmol h –1 g –1 CH 4 , 0.48 μmol h –1 g –1 CO, and 4.23 μmol h –1 g –1 O 2 in a pure water environment (Figure S4b). Additionally, when triethanolamine (TEOA) was used as a sacrificial agent, Eu 2 Ti 4 exhibited a 38.16 μmol h –1 g –1 CO production rate and a 1.41 μmol h –1 g –1 CH 4 production rate (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under AM 1.5G illumination, the Eu 2 Ti 4 dispersed on FTO showed a 0.009 μmol h –1 cm –2 CH 4 production rate and a 0.037 μmol h –1 cm –2 CO production rate for photocatalytic CO 2 reduction in a water vapor atmosphere (Figure f), with a solar-to-fuel (STF) efficiency of 0.0046% (Figure S3). The photocatalytic performance of Eu 2 Ti 4 on an Au-coated FTO substrate is illustrated in Figure S4a, showing an increased selectivity for CH 4 following the Au coating, suggesting that Au can facilitate the separation of electron–hole pairs for CH 4 formation which needs more active electrons. , Moreover, when dispersed in pure water under a CO 2 atmosphere, Eu 2 Ti 4 demonstrated production rates of 2.02 μmol h –1 g –1 CH 4 , 0.48 μmol h –1 g –1 CO, and 4.23 μmol h –1 g –1 O 2 in a pure water environment (Figure S4b). Additionally, when triethanolamine (TEOA) was used as a sacrificial agent, Eu 2 Ti 4 exhibited a 38.16 μmol h –1 g –1 CO production rate and a 1.41 μmol h –1 g –1 CH 4 production rate (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic performance of Eu 2 Ti 4 on an Au-coated FTO substrate is illustrated in Figure S4a, showing an increased selectivity for CH 4 following the Au coating, suggesting that Au can facilitate the separation of electron−hole pairs for CH 4 formation which needs more active electrons. 29,30 Moreover, when dispersed in pure water under a CO 2 atmosphere, Eu 2 Ti 4 demonstrated production rates of 2.02 μmol h −1 g −1 CH 4 , 0.48 μmol h −1 g −1 CO, and 4.23 μmol h −1 g −1 O 2 in a pure water environment (Figure Kelvin probe force microscopy (KPFM) 37 was employed to investigate the electron transfer feature between BiVO 4 and Eu 2 Ti 4 in the heterostructure (Figure 3). Surface potential distribution analysis revealed that the work functions (WFs) of BiVO 4 and Eu 2 Ti 4 are determined to be 4.91 and 4.74 eV, respectively (Figure S10).…”
Section: Introductionmentioning
confidence: 99%
“…BiOCl nanosheets were synthesized by a hydrothermal method. 29 Briefly, Bi(NO 3 ) 3 ·5H 2 O (4 mmol) and NaCl (4 mmol) were dispersed in ethylene glycol (35 mL) and deionized water (5 mL) under vigorous stirring. Then, the mixture was transferred to a Teflon liner and heated at 160 °C for 8 h. After naturally cooling to room temperature, the products were washed with deionized water and ethanol and then dried at 60 °C in a vacuum oven.…”
Section: Methodsmentioning
confidence: 99%
“…S9) and catalytic performance, the activation of CO2 to •CO − 2 was firstly achieved by shoving photo-induced electrons to the adsorbed CO2 molecules. HCO − 3 species then generated from •CO − 2 and •OH radicals, and could further produce the CO and C1 fuels 57 . Besides, the CO3 2− and HCOO − species were intermediates to transform into CO products in the process of photocatalytic CO2 conversion 58,59 .…”
Section: Possible Photocatalytic Mechanismmentioning
confidence: 99%